Convulsions in 2 Patients After Bilateral Ultrasound-Guided Transversus Abdominis Plane Blocks for Cesarean Analgesia. Issue 3 (1st May 2014) - Weiss, Emmanuel; Jolly, Claude; Dumoulin, Jean-Louis; Meftah, Riadh Ben; Blanié, Pierre; Laloë, Pierre-Antoine; Tabary, Nicolas; Fischler, Marc; Le Guen, Morgan
Abstract : Objective: Transversus abdominis plane (TAP) block is commonly used for postcesarean section analgesia and compares favorably with other systemic and regional analgesia techniques. No major complications of ultrasound-guided TAP block have previously been reported in this indication. We report 2 cases of systemic local anesthetic toxicity in this context leading to seizures and treated with lipid emulsion. Case Report: The first event occurred 10 minutes after ultrasound-guided bilateral injections, each consisting of 20 mL of levobupivacaine 3.75 mg/mL. Two episodes of tonic-clonic seizure required resuscitation measures and 200 mL of lipid emulsion. The second case 25 minutes after a 20-mL bilateral injection of ropivacaine 7.5 mg/mL. One generalized tonic-clonic seizure required bag-mask ventilation and 250 mL of lipid emulsion. In both cases, patients were successfully treated and fully recovered. Conclusions: These cases cast a cautionary note for the use of TAP blocks after cesarean delivery. The risk of systemic local anesthetic toxicity after this procedure remains unknown in this population and plasma concentration of local anesthetics should be measured in case of suspected toxicity. To limit this risk, a low concentration of local anesthetic solution should be chosen when a "20 mL bilaterally" regimen is necessary to achieve the required spread for a successful block.